(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Uzbek scientists have done a lot of work in all areas of Islamic Science. In our country, along with Hadith, aqidah, Islamic Fiqh, tafsir and other fields, the science of mysticism has developed. This article provides information about the great muhaddis scientist of our country, Hakim at-Termiziy, his life, scientific m'rosi and interpretation of philosophy.